Penerapan Network Monitoring System Berbasis SNMP untuk Deteksi Dini Gangguan Jaringan - Aritonang, Mhd Adi Setiawan; Jonas Simanullang, Maradona (Pustaka Galeri Mandiri, 2025)
Network stability plays a crucial role in maintaining the quality of digital services in modern organizations. Network disruptions such as packet loss, latency, and downtime often degrade overall system performance. This research implements a Network Monitoring System based on the Simple Network Management Protocol (SNMP) to enable early detection of network disturbances in real time.An experimental approach was conducted by evaluating key performance parameters, including response time, packet loss, availability, and automatic alert frequency. The results show a significant improvement in network performance after implementing the system: the average response time decreased from 180 ms to 52 ms, packet loss dropped from 7.5% to 0.8%, and network availability increased from 94.2% to 99.5%. In addition, the system successfully generated automatic alerts when network anomalies were detected. These findings demonstrate that the SNMP-based monitoring system effectively enhances network reliability and accelerates fault detection processes. The implementation of SNMP provides an efficient and proactive approach for network administrators to maintain service stability and minimize downtime. Keywords: Network Monitoring System, SNMP, Early Detection, Network Performance, Availability